2019
DOI: 10.1002/admi.201801690
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Activated Amorphous Iron Borides (FexB) as Efficient Electrocatalysts for Oxygen Evolution Reaction

Abstract: The development of efficient and earth‐abundant water‐splitting electrocatalysts is of great importance for energy conversion and storage technologies. In this study, surface‐activated amorphous FexB catalysts, Fe–B–O@Fe2B and Fe–B–O@FeB2, are synthesized and remarkable activity for the oxygen evolution reaction (OER) is achieved, e.g., Fe–B–O@FeB2 delivering a current density of 10 mA cm−2 at overpotential of 260 mV with Tafel slope of 57.9 mV dec−1 for OER in alkaline electrolyte. Iron oxide/hydroxide and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…In spite of the related researches are prevailed, it is still noteworthy that these methods appeared some drawbacks of requiring complicated and hash experiment processes, or involving high cost and toxic reagents, as a result, limiting their practical applications. Meanwhile, inspired by the properties of adhesive foot proteins in marine mussels, [29][30][31][32][33] Messersmith and his coworkers first demonstrated that dopamine could spontaneously polymerize and universally deposit onto a variety surfaces under extremely mild alkaline solutions, and the resultant polydopamine (PDA) could be served as versatile platforms through diverse secondary reactions. Moreover, further researches revealed that the oxidative selfpolymerization behavior could be easily tuned by varying the factors, including oxidant, 34,35 pH, 31 temperature, 33 deposited time, 36,37 dopamine concentration, 19 and buffer solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the related researches are prevailed, it is still noteworthy that these methods appeared some drawbacks of requiring complicated and hash experiment processes, or involving high cost and toxic reagents, as a result, limiting their practical applications. Meanwhile, inspired by the properties of adhesive foot proteins in marine mussels, [29][30][31][32][33] Messersmith and his coworkers first demonstrated that dopamine could spontaneously polymerize and universally deposit onto a variety surfaces under extremely mild alkaline solutions, and the resultant polydopamine (PDA) could be served as versatile platforms through diverse secondary reactions. Moreover, further researches revealed that the oxidative selfpolymerization behavior could be easily tuned by varying the factors, including oxidant, 34,35 pH, 31 temperature, 33 deposited time, 36,37 dopamine concentration, 19 and buffer solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, inspired by the properties of adhesive foot proteins in marine mussels, [29][30][31][32][33] Messersmith and his coworkers first demonstrated that dopamine could spontaneously polymerize and universally deposit onto a variety surfaces under extremely mild alkaline solutions, and the resultant polydopamine (PDA) could be served as versatile platforms through diverse secondary reactions. Moreover, further researches revealed that the oxidative selfpolymerization behavior could be easily tuned by varying the factors, including oxidant, 34,35 pH, 31 temperature, 33 deposited time, 36,37 dopamine concentration, 19 and buffer solutions. 38,39 Given that, one can envisage that the materials possess desired gradient physical or chemical properties could be fabricated by the design and construction of PDA gradients, which have been reported by several researches lately.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some boranes (e.g., B 2 H 6 , B 5 H 9 ) as volatile precursors were applied in the chemical vapor deposition (CVD) synthesis of boride nanowires, [57][58][59] while borohydrides (e.g., KBH 4 , NaBH 4 ) were widely involved in solution synthesis routes to obtain amorphous (or low crystalline) boride nanostructures. [60][61][62][63][64][65][66][67] Elemental boron or alkaline-earth borides (e.g., MgB 2 ) were available for solid phase reduction of metal sources, accompanied by the generation of boride particles. [68][69][70] Very recently, our group employed the boron thermal reaction between boron powder and metal oxide under KCl-NaCl molten salt conditions to prepare phase-pure borides ( Fig.…”
Section: Thermal Reduction Routementioning
confidence: 99%
“…9 While the latter approach is not environmentally benign and deteriorates the purity of produced hydrogen with carbon dioxide (CO 2 ), that is, a side product, 10 the former approach comes forward with a huge capacity to generate highly pure CO 2 -free hydrogen 4,11 with electric power from renewable energy resources. 12,13 Simply, the electrolysis of water occurs via the two half-reactions that are the reduction of water at the cathodic electrolyzer, that is, the hydrogen evolution reaction (HER), and the oxidation of water at the anodic electrolyzer, that is, the oxygen evolution reaction (OER). 10,14 The practical application of such an energy-consuming process can come to life only at the expense of high overpotential.…”
Section: Introductionmentioning
confidence: 99%
“…11 In this sense, the fabrication of inexpensive, efficient, durable, and scalable electrocatalysts for the sake of this process is of paramount importance. 12,13 Attempts thus have been made to replace the Pt/C (benchmark HER catalyst) and RuO 2 /IrO 2 (benchmark OER catalysts) with transition metal (TM) selenides, sulfides, nitrides, phosphides, carbides, phosphates, oxides/hydroxides, and borides. 7,[15][16][17] Among these earth-abundant materials, borides have been gaining fame for their robustness in alkaline media.…”
Section: Introductionmentioning
confidence: 99%